Comparative Analysis of Facial Expression Detection Techniques Based on Neural Network - Mohan, Yogendra; Tripathi, Vikas (International Journal of Engineering and Technology, 2018)
Face detection is a critical part of vision and a robot needs to identify a human accurately. A human face undergoes several states of facial expression in a day. Many object detection techniques are applied to identify a facial expression from a digital image or a video frame. Each object detection technique has its own benefits. The overall objective of this paper is to explore the benefits and limitation of existing techniques and provide a comparative analysis. Neural network based facial expression detection technique has demonstrated potential benefits over existing facial expression detection techniques.
Keywords: Object Detection; Robotics; Pattern Recognition; Neural Network; Facial Expression; Computer Vision